Improving patient safety during intrahospital transportation of mechanically ventilated patients with critical illness. Issue 2 (20th April 2020) - Lin, Shwu-Jen; Tsan, Chin-Yuan; Su, Mao-Yuan; Wu, Chao-Ling; Chen, Li-Chin; Hsieh, Hsiu-Jung; Hsiao, Wei-Ling; Cheng, Jui-Chen; Kuo, Yao-Wen; Jerng, Jih-Shuin; Wu, Huey-Dong; Sun, Jui-Sheng
Abstract : Aim: Intrahospital transportation (IHT) of patients under mechanical ventilation (MV) significantly increases the risk of patient harm. A structured process performed by a well-prepared team with adequate communication among team members plays a vital role in enhancing patient safety during transportation. Design and implementation: We conducted this quality improvement programme at the intensive care units of a university-affiliated medical centre, focusing on the care of patients under MV who received IHT for CT or MRI examinations. With the interventions based on the analysis finding of the IHT process by healthcare failure mode and effects analysis, we developed and implemented strategies to improve this process, including standardisation of the transportation process, enhancing equipment maintenance and strengthening the teamwork among the transportation teammates. In a subsequent cycle, we developed and implemented a new process with the practice of reminder-assisted briefing. The reminders were printed on cards with mnemonics including 'VITAL' (Vital signs, Infusions, Tubes, Alarms and Leave) attached to the transportation monitors for the intensive care unit nurses, 'STOP' (Secretions, Tubes, Oxygen and Power) attached to the transportation ventilators for the respiratory therapists and 'STOP' (Speak-out, Tubes, Others and Position) attached to the examination equipment for the radiology technicians. We compared the incidence of adverse events and completeness and correctness of the tasks deemed to be essential for effective teamwork before and after implementing the programme. Results: The implementation of the programme significantly reduced the number and incidence of adverse events (1.08% vs 0.23%, p=0.01). Audits also showed improved teamwork during transportation as the team members showed increased completeness and correctness of the essential IHT tasks (80.8% vs 96.5%, p<0.001). Conclusion: The implementation of reminder-assisted briefings significantly enhanced patient safety and teamwork behaviours during the IHT of mechanically ventilated patients with critical illness.